Consumption Intentions toward green restaurants: Application of theory of planned behavior and altruism - Ying-Pei Shen (International Journal of Management, Economics and Social Sciences (IJMESS), 2017)
Testing 429 valid questionnaires distributed in 20 green restaurants located in Taipei, Taichung, and Kaohsiung, this study explored the intentions of consumers to dine at green restaurants based on their perceptions of green restaurant attributes and their attitudes, subjective norms, and perceived behavioral control toward green restaurants. The results of this study indicated that the perceptions of green restaurant attributes positively influenced consumers' attitudes toward green restaurants, which in turn positively influenced their intentions to visit green restaurants. In addition, consumers' subjective norms and perceived behavioral control both positively influenced consumption intentions regarding green restaurants. We used altruism as the moderating variable in this study. The results indicated that altruism exhibited a strong and significant influence on the relationship between attitude and consumption intentions. In order to promote green restaurants, managers must examine how the restaurant industry, government units, and academic units can contribute to enable the dining industry to meet international standards and cater to the international trends of the "chimney-free" dining industry.
Keywords: D03; M31; 330; Green restaurants; attributes perception; theory of planned behavior; altruism; consumption intentions; chimney-free dining industry